2015
DOI: 10.1186/s13012-016-0478-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leadership hubs on the uptake of evidence-informed nursing practices and workplace policies for HIV care: a quasi-experimental study in Jamaica, Kenya, Uganda and South Africa

Abstract: BackgroundThe enormous impact of HIV on communities and health services in Sub-Saharan Africa and the Caribbean has especially affected nurses, who comprise the largest proportion of the health workforce in low- and middle-income countries (LMICs). Strengthening action-based leadership for and by nurses is a means to improve the uptake of evidence-informed practices for HIV care.MethodsA prospective quasi-experimental study in Jamaica, Kenya, Uganda and South Africa examined the impact of establishing multi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 74 publications
0
43
0
Order By: Relevance
“…Review of the titles and abstracts identified 80 studies for full-text examination, after which 19 studies were found to meet criteria regarding the outcome of interest (enacted healthcare stigma), the study population (healthcare workers) and study design (intervention; Figure 1). Most of the studies were published as full articles in peer reviewed journals [44][45][46][47][48][49][50][51][52][53][54][55][56][57], with the remainder published as conference abstracts [58][59][60] or public reports [61][62][63] (Table 1). According to the World Bank geoscheme [89], a third of studies were located in sub-Saharan Africa [45,48,57,59,61,63,83] followed by South Asia [44,54,55,58,60,62].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Review of the titles and abstracts identified 80 studies for full-text examination, after which 19 studies were found to meet criteria regarding the outcome of interest (enacted healthcare stigma), the study population (healthcare workers) and study design (intervention; Figure 1). Most of the studies were published as full articles in peer reviewed journals [44][45][46][47][48][49][50][51][52][53][54][55][56][57], with the remainder published as conference abstracts [58][59][60] or public reports [61][62][63] (Table 1). According to the World Bank geoscheme [89], a third of studies were located in sub-Saharan Africa [45,48,57,59,61,63,83] followed by South Asia [44,54,55,58,60,62].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study was conducted in the Middle East and Northern Africa [53] (Figure 2). Additionally, two studies had sites in multiple countries, most of which were collectively located in sub-Saharan Africa [47], but one of which also had a single site in Latin American and the Caribbean [56]. The most common study design was a single group pre/post-test comparison [44,45,47,51,52,54,57,59,60,62,63] followed by pre/post-test comparisons with a control group [46,49,55,56,58,61,63] (including one that used a comparative effectiveness trial design [49]) and RCTs [48,50,75].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Action research on the initiative suggests absorptive capacity can be strengthened and consequently improve evidencebased HIV care but only if the initiatives are formally mainstreamed into the health authorities which can sustain them. 102 A qualitative study involving interviews with health-care leaders in Ethiopia, Ghana, Liberia, and Rwanda identified five key themes central to effective leadership: "having an aspirational, valuebased vision for improving the future health of the country; being self-aware and having the ability to identify and use complementary skills of others; investing in and managing relationships; using data in decision making; and sustaining a commitment to learning". 103 The study identified a gap in the use of data to monitor and improve performance.…”
Section: Strategic Leadershipmentioning
confidence: 99%